Absolute optical absorption cross-section measurement of Rb atoms injected into superfluid helium using energetic ion beams. (20th December 2018) - Imamura, Kei; Matsuo, Yukari; Kobayashi, Wataru; Egami, Tsuyoshi; Sanjo, Makoto; Takamine, Aiko; Fujita, Tomomi; Tominaga, Daiki; Nakamura, Yutaro; Furukawa, Takeshi; Wakui, Takashi; Ichikawa, Yuichi; et al.
Abstract: We report on a new in situ laser spectroscopy technique using superfluid helium and a highly energetic ion beam. In taking advantage of superfluid helium as a host matrix for laser spectroscopy, we were able to develop an extremely low background detection system. The first demonstration using 85 Rb 31+ ion beam (66 MeV/nucleon) accelerated at the RIKEN accelerator facility shows improvement of detection limit by two orders of magnitude. A quantitative evaluation of Rb atoms in the observation region enables an analysis of their optical absorption cross-section in superfluid helium from the fluorescence intensity dependence on ion-beam intensity and applied laser power.